1995
DOI: 10.1007/bf01839281
|View full text |Cite
|
Sign up to set email alerts
|

Pentoxifylline pretreatment fails to block the acute-phase response toEscherichia coli endotoxin in dwarf goats

Abstract: The purpose of this study was to assess whether pentoxifylline, a drug that can inhibit the production and action of pro-inflammatory cytokines, had beneficial effects on the acute-phase response to E. coli endotoxin in the dwarf goat. First, the effects of 0.5 mg/kg per min pentoxifylline given intravenously over 15 min were examined in five goats. One week later, the clinical changes caused by i.v. injection of E. coli endotoxin (LPS: 0.1 microgram/kg) were determined. This endotoxin induced fever, tachycard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Pentoxifylline (PTX) is a methyl xanthine derivative and a non-specific phosphodiesterase inhibitor. This drug has anti-inflammatory and antithrombotic properties, and has been used in the clinical treatment of vascular disorders to reduce blood viscosity [ 59 , 60 ]. It has been demonstrated that PTX increases the intracellular levels of c-AMP by inhibition of phosphodiesterase enzymes that hydrolyze c-AMP.…”
Section: Discussionmentioning
confidence: 99%
“…Pentoxifylline (PTX) is a methyl xanthine derivative and a non-specific phosphodiesterase inhibitor. This drug has anti-inflammatory and antithrombotic properties, and has been used in the clinical treatment of vascular disorders to reduce blood viscosity [ 59 , 60 ]. It has been demonstrated that PTX increases the intracellular levels of c-AMP by inhibition of phosphodiesterase enzymes that hydrolyze c-AMP.…”
Section: Discussionmentioning
confidence: 99%